Matrix transformations of Norlund–Orlicz difference sequence spaces of nonabsolute type and their Toeplitz duals - Kilicman, Adem; Raj, Kuldip (SpringerOpen, 2020)
In this paper, the Nörlund–Orlicz difference sequence space Nt(F,Δmn,u,q) of nonabsolute type is introduced as a domain of Nörlund means which is isomorphic to the space ℓ(p) and the basis of the space is constructed. Additionally, the α−, β−, and γ-duals of the spaces are computed and their matrix transformations are given. Finally, the properties like rotundity, modularity of the newly formed spaces are established.